DESIGN AND CONSTRUCTION OF AUGMENTED REALITY X-RAY LEARNING MEDIA WITH DUBBING SYSTEM AT AVIATION POLYTECHNIC SURABAYA - Pramesti, Safira Whinar; Pambudiyatno, Nyaris; Hariyadi, Slamet (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
In the world of vocational education, innovative learning media is essential to improve understanding of technical and complex materials. In the learning process of the Goods and Person Inspection Detection Equipment course at the Surabaya Aviation Polytechnic, there are limited interactive and safe learning media to learn the structure and workings of X-Ray machines, where the use of real tools has radiation risks and limited access. Therefore, this study aims to Design and build Augmented Reality (AR)-based learning media equipped with a Dubbing system and visualizes X-Ray machine components in three dimensions and provides explanatory audio narration. The Development method used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). In the Analysis stage, learning needs are identified and data are collected. The Design stage includes system Design, starting from the X-Ray machine visualization concept to the integration of the DUBBING system as an audio narration. Next, in the Development stage, learning media is developed using supporting software and initial testing of system functionality is carried out. Implementation by applying the developed media in the learning environment. Finally, Evaluation, an assessment of the feasibility and effectiveness of the learning media was carried out with the results of validation tests from media experts and respondents, so that media that is suitable for use in the learning process was obtained. The results of the study showed that this AR X-Ray media can be operated via a smartphone device equipped with interactive features so that it supports the delivery of material accompanied by voice narration. Based on the validation results by users and media experts, this media was declared suitable for use in the learning process and was proven to improve cadets’ understanding of the material and be a safer and more interesting alternative to conventional methods.